2012
DOI: 10.1146/annurev-publhealth-031811-124542
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Infant Mortality and Effective, Equitable Care: Are Infants Suffering from Benign Neglect?

Abstract: Quality care for infant mortality disparity elimination requires services that improve health status at both the individual and the population level. We examine disparity reduction due to effective care and ask the following question: Has clinical care ameliorated factors that make some populations more likely to have higher rates of infant mortality compared with other populations? Disparities in postneonatal mortality due to birth defects have emerged for non-Hispanic black and Hispanic infants. Surfactant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…29-34 However, this is the first report of maternal racial/ethnic identity as a predictor of oral feeding progression for preterm infants. This was especially surprising given that infants of Latina versus African-American mothers had higher birthweights (mean = 1844 and 1733, respectively, p = 0.08) and higher five-minute Apgar scores (mean = 8.61 and 7.85, respectively, p < 0.0001), on average.…”
Section: Discussionmentioning
confidence: 85%
“…29-34 However, this is the first report of maternal racial/ethnic identity as a predictor of oral feeding progression for preterm infants. This was especially surprising given that infants of Latina versus African-American mothers had higher birthweights (mean = 1844 and 1733, respectively, p = 0.08) and higher five-minute Apgar scores (mean = 8.61 and 7.85, respectively, p < 0.0001), on average.…”
Section: Discussionmentioning
confidence: 85%
“…There are modest and mixed findings regarding disparities in vaginal birth after caesarean, nonindicated early-term birth, and primary caesarean section (76,85,102); steroids during preterm labor (90,120); and surfactants for preterm infants (71,75). It is not clear if disparities reflect within-or between-provider effects or unmeasured morbidity.…”
Section: Obstetrical Carementioning
confidence: 99%
“…Some studies have reported lower prenatal utilization rates in Black people compared to other races, particularly early in pregnancy. This intentional underutilization of prenatal care has been suggested through patient interviews to be due in part to exposure to institutionalized racism and perceived bias when presenting to medical attention [ 8 , 9 , 10 ]. While later presentation to care may negatively impact maternal and infant outcomes, recent trends suggest the gap in prenatal care utilization is rapidly closing between races so access to care does not fully explain the disparities in birth outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%